O Elo Perdido: o Conselho de Desenvolvimento Econômico do Espírito Santo-CODEC (1950-1980) - Ribeiro, Diones Augusto (2016)
The thesis aims to understand the importance of the Conselho de Desenvolvimento Econômico do Espírito Santo (Codec) for public policies designed to modernize the Espírito Santo - considering the per capita levels of São Paulo, Rio de Janeiro and Minas Gerais - through planning and industrialization, between the years 1950 and 1980. The Codec was the locus where part of the proposals, aimed at Espírito Santo capitalist development, were intended, in view of the need to reorient the local economy to the changes brought about by the eradication of coffee plantations and the different projects industrial formulated for the development of the local economy, due to the state political game which saw industrialization as a means of political hegemony. The final synthesis of such projects were the great impact projects, which reinforced the complementary position of the state economy on the world stage by fixing the big mining, steel and pulp. Political, economic and social changes promoted aimed suit the local economy to international capitalism through the public capital partnership with the private, without significant structural changes. There was intense concentration of wealth and land, especially in the metropolitan area of the Grande Vitória, "heart" of major projects.